Beneficial changes in food consumption and nutrient intake after 10 years of follow-up in a Mediterranean cohort: the SUN project. (December 2016) - de la Fuente-Arrillaga, Carmen; Zazpe, Itziar; Santiago, Susana; Bes-Rastrollo, Maira; Ruiz-Canela, Miguel; Gea, Alfredo; Martinez-Gonzalez, Miguel
Abstract Background The assessment of changes in dietary habits provides interesting information on whether or not the observed trends are in line with accepted nutritional guidelines. The objective was to evaluate within-subject longitudinal changes in food consumption and nutrient intake and in a 10-year follow-up study. Methods The SUN (Seguimiento Universidad de Navarra ) project is a prospective Spanish cohort study. Diet was assessed using a 136-item food-frequency questionnaire (FFQ), previously validated in Spain. The participants were 3036 university graduates (55.8 % women) of Spain and the main outcome measures the changes in dietary quality and in food consumption and nutrient intake. Paired t-tests and conditional logistic regression models were used to evaluate within-subject longitudinal dietary changes and the risk of inadequacy respectively, after 10 years of follow-up. Results During follow-up, participants showed a relevant and significant increase (p < 0.001) in the consumption of fruits (7.4 %), vegetables (8.6 %), low-fat dairy products (35.2 %), lean meat (12.4 %), fish (2.9 %), whole grains (53.2 %), nuts (52.4 %) and a significant decrease in legumes (−7.4 %), whole-fat dairy products (−44.2 %), red meat (−17.6 %), sugar-sweetened beverages (−58.7 %) and wine (−11.9 %). With respect to nutrients, we found a higher proportion of carbohydrates (3.6 %) and fiber (7.4 %) and a decrease in total energy intake (2.7 %), total fat (−4.5 %), SFA (−9.4 %), MUFA (−4.9 %), PUFA (−12.7 %), w-3 and w-6 fatty acids (−9.1 and −20.5 % respectively) and cholesterol (−9.6 %). Conclusions In this Mediterranean cohort study, mainly beneficial changes in the consumption of most foods and macronutrients were observed after 10 years of follow-up.